2017
DOI: 10.1200/jco.2016.69.8480
|View full text |Cite|
|
Sign up to set email alerts
|

Validation and Modification of a Prediction Model for Acute Cardiac Events in Patients With Breast Cancer Treated With Radiotherapy Based on Three-Dimensional Dose Distributions to Cardiac Substructures

Abstract: PurposeA relationship between mean heart dose (MHD) and acute coronary event (ACE) rate was reported in a study of patients with breast cancer (BC). The main objective of our cohort study was to validate this relationship and investigate if other dose-distribution parameters are better predictors for ACEs than MHD.Patients and MethodsThe cohort consisted of 910 consecutive female patients with BC treated with radiotherapy (RT) after breast-conserving surgery. The primary end point was cumulative incidence of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
274
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(312 citation statements)
references
References 46 publications
6
274
3
7
Order By: Relevance
“…Another question is whether some cardiac subvolumes should take priority over others during the treatment planning process. 810 Our data provide preliminary information linking cardiac subvolume dose to subsequent toxicity. Given that the three event types showed different patterns of associations with heart subvolumes, it seems advisable to minimize dose to the entirety of the heart if possible.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Another question is whether some cardiac subvolumes should take priority over others during the treatment planning process. 810 Our data provide preliminary information linking cardiac subvolume dose to subsequent toxicity. Given that the three event types showed different patterns of associations with heart subvolumes, it seems advisable to minimize dose to the entirety of the heart if possible.…”
Section: Discussionmentioning
confidence: 77%
“…38,39 In a recent analysis of over 900 patients with breast cancer treated with radiation, van den Bogaard et al reported that LV dose had the greatest association with ischemic events. 10 Thus, the common perception that acute coronary syndrome is related to LV dose may also apply to patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cardiac damage was shown to be correlated with the mean heart dose, with 7.4% rate increase of acute coronary events per one Gray (95% confidence interval, 2.9-14.5; P<0.001), with no minimum threshold for risk [8]. The risk of acute coronary events within the first 9 years after RT was recently confirmed by an additional publication [12], showing significant relationships between cardiac radiation dose and the incidence of acute coronary events. Therefore, as there appears to be no threshold dose below which cardiac complications do not appear, radiation-induced cardiac diseases remain potential severe late complications of BC RT.…”
Section: Introductionmentioning
confidence: 64%
“…[3]. На основании резуль-татов исследования авторы сделали вывод о том, что доза 5 Гр, подведенная к левому желудочку сердца, является важным прогностическим фактором параметра доза-объем [4].…”
unclassified